Data from: Partial genomic survival of cave bears in living brown bears - Barlow, Axel; Cahill, James A.; Hartmann, Stefanie; Theunert, Christoph; Xenikoudakis, Georgios; Fortes, Gloria G.; Paijmans, Johanna L. A.; Rabeder, Gernot; Frischauf, Christine; Grandal-D'Anglade, Aurora; García-Vázquez, Ana; Murtskhvaladze, Marine; et al. (Data Archiving and Networked Services (DANS), 2019)
Although many large mammal species went extinct at the end of the Pleistocene epoch, their DNA may persist due to past episodes of interspecies admixture. However, direct empirical evidence of the persistence of ancient alleles remains scarce. Here, we present multifold coverage genomic data from four Late Pleistocene cave bears (Ursus spelaeus complex) and show that cave bears hybridized with brown bears (Ursus arctos) during the Pleistocene. We develop an approach to assess both the directionality and relative timing of gene flow. We find that segments of cave bear DNA still persist in the genomes of living brown bears, with cave bears contributing 0.9 to 2.4% of the genomes of all brown bears investigated. Our results show that even though extinction is typically considered as absolute, following admixture, fragments of the gene pool of extinct species can survive for tens of thousands of years in the genomes of extant recipient species. 191Y_arctos_Slovenia_haploidised_fastaHaploidised fasta sequence generated by mapping Illumina short reads to the reference genome assembly of the giant panda, then randomly selecting a single high quality nucleotide from the read stack for each position of the reference genome. See the original publication for full details. The raw sequencing data is also available from the European Nucleotide Archive. Note that this file will contain abundant errors in comparison to a consensus base call from high coverage data.191Y_rep1_all.fa.gz235_arctos_Russia_haploidised_fastaHaploidised fasta sequence generated by mapping Illumina short reads to the reference genome assembly of the giant panda, then randomly selecting a single high quality nucleotide from the read stack for each position of the reference genome. See the original publication for full details. The raw sequencing data is also available from the European Nucleotide Archive. Note that this file will contain abundant errors in comparison to a consensus base call from high coverage ...